The advantages of flow cytometry in comparison to fluorometric measurement in algal toxicity test - Eleršek, Tina (Acta biologica slovenica, 2012)
Fluorometric measurements in algal toxicity tests are very commonly used as surrogate parameters for algal biomass. Although, fluorometry is a powerful technique, we have demonstrated that it is not suitable for determination of toxic effects of chemicals, which alter the fluorescence spectra. We recommendthe flow cytometry as the best technique for detecting algal and/or cyanobacterial cell count and fluorescence per cell. Flow cytometry has many advantages: little volume of algal/cyanobacterial sample required, suitable also for little algal/cyanobacterial cells, distinction between live and dead cells. Furthermore, flow cytometry reveals the early changes in fluorescence spectra as a consequence of the specific chemicals presence or stress, even though the cell count is not yet affected (an early marker for ecotoxicology testing).
Keywords: algae; alge; cianobakterije; cyanobacteria; ecotoxicity test; ekotoksikološki test; flow cytometry; fluorescenca; fluorescence; pretočna citometrija